Behavior problems in sexually abused preschoolers over a 1-year period: The mediating role of attachment representations. (23rd April 2018) - Charest, Florence; Hébert, Martine; Bernier, Annie; Langevin, Rachel; Miljkovitch, Raphaële
Abstract: According to the developmental psychopathology framework, adverse childhood experiences, including child sexual abuse (CSA), may alter the course of normal development in children. Attachment security has been identified as a protective factor against psychopathology and may thus play a critical role in predicting victims' adaptation. The main objective of the present study was to investigate the mediating effect of attachment representations in the relation between CSA and behavior problems over a 1-year period. The sample consisted of 391 children (251 sexually abused) aged 3.5 to 6 years. The Attachment Story Completion Task and the Child Behavior Checklist were used. Disorganized attachment partially mediated the relation between CSA and children's internalizing and externalizing behavior problems 1 year following the initial assessment. This mediation effect was not found for ambivalent nor secure attachment dimensions. Child gender was found to moderate the association between CSA and disorganization, with larger effects of CSA among boys. These findings underscore the importance of considering attachment representations in treatment programs for preschool victims. Evidence-based practice focusing on trauma could be combined with an attachment-based intervention targeting the parent–child relationship. Moreover, interventions should be gender sensitive, as CSA appears to affect boys and girls differently.